Feasibility of Learning Management System for Community-Based Learning Assessment According to the Student's Perspective (Future Science, 2022)
The assessment of learning in the community in the Kampung Pelita Medika (KPM) program of the Medical Faculty of Universitas Riau has been carried out as a physical portfolio. Physical portfolio causes problems due to accumulating working papers, manually inputting data, and the non-integration of data. One of the things that can be done is to use a Learning management system (LMS). The study aims to design an LMS-based assessment system suitable for the KPM program and assess its ability to be implemented according to student perspectives. The survey was conducted on 30 students using quantitative and qualitative approaches. Data was taken by filling out the LMS proficiency satisfaction questionnaire and open-ended questions. Research showed that 37% uploaded on time, 50% were late, and 13% did not upload. Most (85 %) stated the LMS was easy to use, 15 % said it was quite difficult, and 0% stated it was difficult. Some obstacles were uploading large documents, unstable internet networks, less informative task commands, and adaptation to the application. Some proposals for improvement were a simpler document upload system, an online checklist feature, and an unsubmit component. This study concluded the LMS-based KPM assessment system was quite feasible to use. However, qualitative data indicate the need for improvements to the upload system and more informative task commands. Further research needs to be done on a larger sample to assess the effectiveness of using the LMS for the assessment system by reviewing applications to lecturers, administrative personnel, and perceived benefits